KADAR LOGAM BERAT TIMBAL (Pb) PADA KERANG DARAH (Anadara granosa) DAN SEDIMEN ASAL PERAIRAN SEDANAU KABUPATEN NATUNA - Linda, Riza; Hartanti, Lucky; Warsidah, Warsidah; Ashari, Asri Mulya; Kurniadi, Bambang (Marinade, 2022)
The waters of Sedanau, Natuna Regency are dense with inter-island ship traffic activities and the construction of piers that can cause pollution to the aquatic environment. The purpose of the study was to determine the concentration of heavy metal content of Pb in blood mussels (Anadara granosa) and its sediments which was carried out in July 2020 at 2 different sampling stations. Station 1 is close to fishing activities, fishing boat traffic docks and inter-island passenger ships, station 2 is close to fishing boat docks and floating net cages but far from fishing activities and ship traffic. Measurement of heavy metal concentrations of Pb using Atomic Absorption Spectrophotometer (AAS) method with reference to the Indonesian National Standard (SNI) Number 06-6992.2-2004 concerning heavy metal testing for Pb. The results of the measurement of the concentration of heavy metal Pb in blood clams (Anadara granosa) and their sediments at station 1 was 0 0.0243 g/g, and 0.0263 g/g, while at station 2 it was 0.0109 g/g, and 0.0233 g/g.